Of ostriches, frogs, birds and lizards: A dynamic framework of cultural identity negotiation strategies in an era of global mobility. Issue 3 (9th September 2019) - Li, Chenchen; Zhang, Ling Eleanor; Harzing, Anne-Wil
Abstract : Purpose: In response to the somewhat paradoxical combination of increasing diversity in the global workforce and the resurgence of nationalism in an era of global mobility, the purpose of this paper is to uncover how employees on international assignments respond to exposure to new cultures. Specifically, the paper aims to explicate the underlying psychological mechanisms linking expatriates' monocultural, multicultural, global and cosmopolitan identity negotiation strategies with their responses toward the host culture by drawing upon exclusionary and integrative reactions theory in cross-cultural psychology. Design/methodology/approach: This conceptual paper draws on the perspective of exclusionary vs integrative reactions toward foreign cultures – a perspective rooted in cross-cultural psychology research – to categorize expatriates' responses toward the host culture. More specifically, the study elaborates how two primary activators of expatriates' responses toward the host culture – the salience of home-culture identity and a cultural learning mindset – explain the relationship between cultural identity negotiation strategies and expatriates' exclusionary and integrative responses, providing specific propositions on how each type of cultural identity negotiation strategy is expected to be associated with expatriates' exclusionary and integrative responses toward the host culture. Findings: The present study proposes that expatriates' adoption of a monocultural identity negotiation strategy is positively associated with exclusionary responses toward the host culture and it is negatively associated with integrative responses toward the host culture; expatriates' adoption of a multicultural identity negotiation strategy is positively associated with both exclusionary responses and integrative responses toward the host culture; expatriates' adoption of a global identity negotiation strategy is negatively associated with exclusionary responses toward the host culture; and expatriates' adoption of a cosmopolitan identity negotiation strategy is negatively associated with exclusionary responses, and positively associated with integrative responses toward the host culture. The following metaphors for these different types of cultural identity negotiation strategies are introduced: "ostrich" (monocultural strategy), "frog" (multicultural strategy), "bird" (global strategy) and "lizard" (cosmopolitan strategy). Originality/value: The proposed dynamic framework of cultural identity negotiation strategies illustrates the sophisticated nature of expatriates' responses to new cultures. This paper also emphasizes that cross-cultural training tempering expatriates' exclusionary reactions and encouraging integrative reactions is crucial for more effective expatriation in a multicultural work environment.